Film Productivity and Matching Frictions in the Labor Markets: Is This Unending Curse to Employers? - Ndolo, David Katuta; Senelwa, Victor Kidake (European Scientific Journal, ESJ, 2023)
Firm productivity behavior is heavily influenced by labor market frictions in both emerging and established countries. Kenya keeps pushing for more effective measures to raise productivity, but the significance of friction in the labor market remains unclear. This study uses cross-sectional data from the Skills Toward Employment Productivity (STEP) Household Survey 2016–2017 for Kenya, sourced from the World Bank database, to examine the impact of market friction on firm productivity. Market friction is defined in terms of overeducation, undereducation, education, and skills mismatch. The findings, which were derived from an estimate of the endogenous switching regression (ESR) using the Full specification of the Maximum Likelihood model, demonstrated that undereducation and skills mismatch considerably lower firm production, whereas the effect of overeducation was negligible. In addition, the marginal treatment effect that is crucial for policymaking revealed that overeducation was substantially linked to higher levels of firm productivity, whereas the education and skills mismatch was linked to lower levels of firm productivity. Implications for policy highlight the need of matching graduates with jobs that are well-suited to their degree and experience levels.